2017
DOI: 10.1128/aac.00969-17
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanism of Action of 5-Nitro-1,10-Phenanthroline against Mycobacterium tuberculosis

Abstract: New chemotherapeutic agents with novel mechanisms of action are urgently required to combat the challenge imposed by the emergence of drug-resistant mycobacteria. In this study, a phenotypic whole-cell screen identified 5-nitro-1,10-phenanthroline (5NP) as a lead compound. 5NP-resistant isolates harbored mutations that were mapped to and were also resistant to the bicyclic nitroimidazole PA-824. Mechanistic studies confirmed that 5NP is activated in an F-dependent manner, resulting in the formation of 1,10-phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 58 publications
(69 reference statements)
4
29
0
1
Order By: Relevance
“…SAR studies revealed that the nitroso group is important for anti-tubercular activity associated with this series. In concordance previous studies have also shown that nitro or nitroso functional groups are essential for the anti-tubercular activity of small molecules (Singh et al, 2008;Kidwai et al, 2017Kidwai et al, , 2019. We also show that substitution at the para-position of the phenyl ring with either electron withdrawing group such as (chloro and cyano) or electron donating groups (such as methyl) improved NSC 18725 activity in vitro.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…SAR studies revealed that the nitroso group is important for anti-tubercular activity associated with this series. In concordance previous studies have also shown that nitro or nitroso functional groups are essential for the anti-tubercular activity of small molecules (Singh et al, 2008;Kidwai et al, 2017Kidwai et al, , 2019. We also show that substitution at the para-position of the phenyl ring with either electron withdrawing group such as (chloro and cyano) or electron donating groups (such as methyl) improved NSC 18725 activity in vitro.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we have performed whole cell based screening and identified 24 scaffolds that possessed anti-mycobacterial activity below 2.5 µM. In concordance, with previous studies, majority of these compounds showed comparable activity against both M. bovis BCG and M. tuberculosis in vitro (Taneja and Tyagi, 2007;Altaf et al, 2010;Stanley et al, 2012;Kidwai et al, 2017). However, NSC 70082, NSC 202998, NSC 338695, and NSC 338181 displayed better activity against M. bovis BCG in comparison to M. tuberculosis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the same study, it has been demonstrated that metformin interferes with mitochondrial respiratory chain, induces the production of reactive oxygen species that results in killing of intracellular bacteria . In addition to metformin, several other small molecules such as nitazoxanide, geftinib, vitamin D, mTOR inhibitors, statins, verapamil, fluoxetine, carbamazepine, calcimycin, 5‐Nitro, 1–10, phenanthroline, and valproic acid inhibits growth of intracellular bacteria by inducing autophagy . Doxycycline inhibits secretion of matrix metalloproteinases, which results in reduced lung tissue damage and M. tuberculosis growth in guinea pigs .…”
Section: Host‐directed Therapiesmentioning
confidence: 99%
“…Autophagy-adjunctive therapeutics is an emerging concept for the improved treatment of TB. Although it is a promising strategy, even for controlling drug-resistant strains, according to in vitro and preclinical studies [72,73,86], current data on its clinical use are insufficient, and more evidence is need in future studies.…”
Section: Challenges and Perspectives Of Autophagyadjunctive Therapeuticsmentioning
confidence: 99%